AKUNTABILITAS DAN TRANSPARANSI DALAM PENGELOLAAN DANA DESA DI DESA TAMANAGUNG, KECAMATAN MUNTILAN, KABUPATEN MAGELANG - Adam Nurfaizi Rosyan; Amn Zarkasyi Rahman; Kismartini Kismartini (Journal of Public Policy and Management Review)
In managing village funds, the Tamanagung Village Government, Muntilan District, Magelang Regency must be able to give trust to the community and good management. However, there is still accountability and budget transparency that is not widely known by the community, as well as several village fund management functions that are not carried out properly, such as improving village infrastructure, which is not balanced with the annual increase in the village fund budget. The purpose of this study was to determine the relationship of accountability to the management of village funds, transparency to the management of village funds, and simultaneously accountability and transparency to the management of village funds. The methodology of this research is qualitative using primary and secondary data. The analytical technique used is field observation, and comparing with theory, as well as previous research. The results of the study show that accountability has a relationship with the management of village funds, also transparency has a relationship with the management of village funds, and together accountability and transparency have a relationship with the management of village funds.